2021
DOI: 10.3390/biology10060561
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Immune-Related Adverse Events—A Consequence of Immune Checkpoint Inhibitor Therapy

Abstract: The advent of immunotherapy has changed the management and therapeutic methods for a variety of malignant tumors in the last decade. Unlike traditional cytotoxic chemotherapy, which works by interfering with cancer cell growth via various pathways and stages of the cell cycle, cancer immunotherapy uses the immune system to reduce malignant cells’ ability to escape the immune system and combat cell proliferation. The widespread use of immune checkpoint inhibitors (ICIs) over the past 10 years has presented valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
2
1
Order By: Relevance
“…Another preclinical study investigated the effects of PD-1 and PD-L1 blockade in an inflammatory arthritis model and observed that PD-1 and/or PD-L1 knockout in young male mice resulted in a significant reduction of bone volume and trabecular thickness and an increase in trabecular separation, overall suggesting a bone loss phenotype when immune checkpoint proteins are inhibited [95] . This study contradicts Wang et al [94] and suggests that PD-1 and PD-L1 are essential for maintaining bone homeostasis, at least in settings of chronic inflammation, and appears to more closely align with clinical reports of bone and joint injuries and increased fracture risk in patients receiving ICIs [85] , [86] , [87] , [88] , [89] , [90] , [91] . These contradictory data, combined with the overall lack of studies investigating the role of ICIs in altering bone microarchitecture, particularly in female pre-clinical models, highlight a need for a more comprehensive examination of this relationship.…”
Section: Immune Related Adverse Events Associated With Ici Therapycontrasting
confidence: 76%
See 1 more Smart Citation
“…Another preclinical study investigated the effects of PD-1 and PD-L1 blockade in an inflammatory arthritis model and observed that PD-1 and/or PD-L1 knockout in young male mice resulted in a significant reduction of bone volume and trabecular thickness and an increase in trabecular separation, overall suggesting a bone loss phenotype when immune checkpoint proteins are inhibited [95] . This study contradicts Wang et al [94] and suggests that PD-1 and PD-L1 are essential for maintaining bone homeostasis, at least in settings of chronic inflammation, and appears to more closely align with clinical reports of bone and joint injuries and increased fracture risk in patients receiving ICIs [85] , [86] , [87] , [88] , [89] , [90] , [91] . These contradictory data, combined with the overall lack of studies investigating the role of ICIs in altering bone microarchitecture, particularly in female pre-clinical models, highlight a need for a more comprehensive examination of this relationship.…”
Section: Immune Related Adverse Events Associated With Ici Therapycontrasting
confidence: 76%
“…In addition to the commonly reported ICI-induced toxicities, patients also present with rheumatologic and musculoskeletal toxicities including arthralgias, which present in up to 43% of patients, and rheumatoid arthritis, which presents in 1–7% of patients [85] , [86] , [87] , [88] , [89] . There are also reports of bone loss and fractures following treatment with ICIs.…”
Section: Immune Related Adverse Events Associated With Ici Therapymentioning
confidence: 99%
“…A more recent study on 80 patients diagnosed with PMR, which were observed for >40 weeks and screened using positron emission tomography/computed tomography (PET/CT) revealed a higher prevalence of cancer in PMR patients, in comparison to the general population (26). Also, the treatment for cancer such as immune checkpoint inhibitors may trigger PMR (27).…”
Section: Pathogenesismentioning
confidence: 99%
“…The bibliographic data were all obtained from the Science Citation Index Expanded (SCI-expanded, 1999-present) of the Web of Science Core Collection (WoSCC). Rheumatic irAEs were identified through literature review (9,11,14). To perform a comprehensive literature search of ICIs associated rheumatic irAEs, specific retrieval rules were designed as follows: #1: TS= (ipilimumab) or TS=(avelumab) or TS=(nivolumab) or TS= (atezolizumab) or TS=(pembrolizumab) or TS=(durvalumab) or TS=(cemiplimab) or TS=(relatimab) or TS=("immune checkpoint inhibitor*") or TS=("immune checkpoint block*") or TS= ("immune checkpoint therap*").…”
Section: Data Sources and Retrieval Strategymentioning
confidence: 99%